1997
DOI: 10.1002/(sici)1097-4628(19971003)66:1<105::aid-app12>3.3.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the growth of Phanerochaete Chrysosporium in a blend of low density polyethylene and sugar cane bagasse

Abstract: Thermogravimetry, differential scanning calorimetry, and wide-angle Xray scattering techniques were used to study changes in the composition, relative heat of fusion, and mean crystal size of blends made from low-density polyethylene (LDPE) and sugar cane bagasse (SCB), before and after exposure to the fungus Phanerochaete chrysosporium for 32 days. The initial blends contained equal weights of each component. The composition of the blend LDPE/SCB at 32 days changed to the value (66 { 3)/(34 { 3). The relative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 2 publications
0
17
1
Order By: Relevance
“…Other studies have found that the crystallinity of polymer films changes with time due to the action of microorganisms [16,18,45], a mech anisms in which an initial increase in crystallinity due to the con sumption of amorphous regions followed by a decrease in crystallinity once microorganisms start to consume small size crystals have been described [18]. However, in this study the effect of biotic treatment was not observed and changes in the crystallinity cannot be attributed to microbial action.…”
Section: Changes In the Crystallinity Of The Polymermentioning
confidence: 49%
“…Other studies have found that the crystallinity of polymer films changes with time due to the action of microorganisms [16,18,45], a mech anisms in which an initial increase in crystallinity due to the con sumption of amorphous regions followed by a decrease in crystallinity once microorganisms start to consume small size crystals have been described [18]. However, in this study the effect of biotic treatment was not observed and changes in the crystallinity cannot be attributed to microbial action.…”
Section: Changes In the Crystallinity Of The Polymermentioning
confidence: 49%
“…Further work is clearly needed to ascertain why some regions in the LLDPE are more susceptible to void formation than others. These might be due to microbial activity on the amorphous portions of LLDPE [45][46][47][48][49]. Further work is clearly needed to verify such speculation.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that, there is an initial increase in the crystallinity of PE after microbial degradation [45][46][47][48][49][50]. Furthermore, microbes generally degrade the amorphous portions of the PE first [45-47, 49, 50], before disrupting the crystalline order [48,51].…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…These crystalline particles are made of crystalline blocks, which are bordered with the second type of amorphous region. 3,39 During oxidation and bacterial treatment, the amorphous region is oxidized and due to this oxidation, smaller crystalline particles are released. 3 In the course of further treatment of polyethylene, smaller crystalline particles are oxidized and further utilized by bacterium, leading to an increase in the amount of larger crystallites.…”
Section: Ft-ir Analysismentioning
confidence: 99%